Detonation Type Ram Accelerator: A Computational Investigation - Bhat, Sunil (Defence Science Journal, 2013)
An analytical model explaining the functional characteristics of detonation type ram accelerator is presented. Major flow processes, namely, (i) supersonic flow over the cone of the projectile, (ii) initiation ofconical shock wave and its reflection from the tube wall, (iii) supersonic combustion, and (iv) expansion wave and its reflection are modelled. Taylor-Maccoll approach is adopted for modellingthe flow over the cone of the projectile. Shock reflection is treated in accordance with wave angle theorytor flows over the wedge. Prandtl-Mayer analysis is used to model the expansion wave and its reflection.Steady one-dimensional flow with heat transfer along with Rayleigh line equation for perfect gases isused to model supersonic combustion. A computer code is developed to compute the thrust producedby combustion of gases. Ballistic parameters like thrust-pressure ratio and ballistic efficiency of the accelerator are evaluated and their maximum values are 0.032 and 0.068, respectively. The code indicates possibility ofachieving high velocity of 7 km/s on utilising gaseous mixture of 2H2+O2 in the operation.Velocity range suitable for operation of the accelerator lies between 3.8 - 7.0 km/s. Maximum thrust valueis 33721 N which corresponds to the projectile velocity of 5 km/s.